Respuesta :

Answer:

x = 1 , y = 0

Step-by-step explanation:

Solve the following system:

{y = 2 x - 2 | (equation 1)

y = x - 1 | (equation 2)

Express the system in standard form:

{-(2 x) + y = -2 | (equation 1)

-x + y = -1 | (equation 2)

Subtract 1/2 × (equation 1) from equation 2:

{-(2 x) + y = -2 | (equation 1)

0 x+y/2 = 0 | (equation 2)

Multiply equation 2 by 2:

{-(2 x) + y = -2 | (equation 1)

0 x+y = 0 | (equation 2)

Subtract equation 2 from equation 1:

{-(2 x)+0 y = -2 | (equation 1)

0 x+y = 0 | (equation 2)

Divide equation 1 by -2:

{x+0 y = 1 | (equation 1)

0 x+y = 0 | (equation 2)

Collect results:

Answer: {x = 1 , y = 0

The solution of given linear system of the equations is given by:

(x,y) = (1,0)

Given system of linear equations is:

[tex]y = 2x - 2\\y = x - 1[/tex]

Solving the equations by using method of substitution:

Putting value of y from first equation in second equation, we get:

[tex]2x - 2 = x - 1\\2x -x = 2 - 1\\x = 1[/tex]

The value of y will be:

[tex]y = x - 1 = 1 -1 = 0[/tex]

Thus,  the solution of the given  system of linear equations is (x,y) = (1,0)

The solution of these equations can be found on the graph where these lines intersect. See the graph given below.

Learn more about linear equations here:

https://brainly.com/question/14491895

Ver imagen astha8579